The Enlightened Patrolman : Early Law Enforcement in Mexico City - Germeten, Nicole von (Book collections on Project MUSE., 2022)
"The Enlightened Patrolman guides readers through Mexico City's efforts to envision and carry out modern values as viewed through the lens of early law enforcement, an accelerated process of racialization of urban populations, and burgeoning ideas of modern masculinity"--